Performance analysis of 2-Point explicit group iterative methods for solving four-point composite closed Newton-Cotes system - Muthuvalu, M.S. (American Institute of Physics Inc., 2016)
In this paper, numerical solutions of second kind Fredholm integral equation on a bounded domain are considered. We convert the integral equation to a linear system by using four-point composite closed Newton-Cotes (4-CCNC) scheme. Then, the performance of 2-Point Explicit Group (2-EG) method with complexity reduction approach for solving the generated linear system is investigated. Numerical results by solving test problems are included to verify the performance of the proposed method. Â© 2016 Author(s).